Essays on Real Business Cycle Modeling and the Public Sector - Aleksandar Vasilev (University of Glasgow, 2013)
This thesis is composed of three core chapters on modern dynamic macroeconomics, which study di erent aspects of the public sector labor market in a large EU economy with sig- ni cant public employment share and a non-trivial public sector wage premium over the private sector labor compensation. The study in this dissertation adds to earlier research by incorporating endogenous government hours and wages in the model framework and argues that the presence of a sizable public sector labor market in European economies generates signi cant interaction with the private sector labor and capital markets. In addition, the presence of interest groups (labor unions, government bureaucracy), as well as other labor market frictions in the public sector, is shown to be an important element of the analysis when discussing scal policy reforms. Motivated by the highly-unionized public sectors, the high public shares in total employ- ment, and the public sector wage premia observed in most post-WWII European economies, Chapter 1 examines the role of public sector unions in a general equilibrium framework. A strong union presence in a large non-market sector is shown to be relevant for both busi- ness cycle uctuations and for the welfare e ect of scal regime changes. To this end, an otherwise standard real-business-cycle (RBC) model is augmented with a public sector union optimization problem. The resulting theoretical setup generates cyclical behavior in government hours and wages that is consistent with data behavior in an economy with a highly-unionized public sector, namely Germany during the period 1970-2007. The main findings of Chapter 1 are: (i) the model with a public sector union performs reasonably well vis-a-vis data; (ii) overall, the public sector union model is a significant improvement over a similar model with exogenous public sector employment; (iii) endogenously-determined pub- lic wage and hours add to the distortionary effect of contractionary tax reforms and produce significantly higher welfare losses. Additionally, the union model requires greater changes in tax rates to achieve a pre-specified increase in tax revenue compared to an equivalent model with exogenous public sector hours. Thus, endogenous public sector hours and wages in the setup are shown to be quantitatively important for public policy evaluation. Ignoring the positive co-movement between public and private hours and wages leads to a significant underestimation of the welfare effect of fiscal regime changes. Chapter 2 characterizes optimal scal policy and evaluates it relative to the exogenous (ob- served) one. Motivated by the high public employment, and the public wage premia observed in the major European economies, a Real-Business-Cycle model, calibrated to German data (1970-2007), is set up with a richer government spending side, and an endogenous private- public sector labor choice. To illustrate the effects of fiscal policy on sectoral allocation of hours, public wage rate determination and the provision of labor-intensive public services, two regimes are compared and contrasted to one another - exogenous vs. optimal (Ramsey) policy case. The main findings from the computational experiments performed in Chapter 2 are: (i) The optimal steady-state capital tax rate is zero, as it is the most distortionary tax to use; (ii) A higher labor tax rate is needed in the Ramsey case to compensate for the loss in capital tax revenue; (iii) Under the optimal policy regime, public sector employment is lower, but government employees receive higher wages; (iv) The benevolent Ramsey planner provides the optimal amount of the public good, and substitutes labor for capital in the input mix for public services and private output; (v) The government wage bill is smaller, while public investment is three times higher than in the exogenous policy case. Lastly, the thesis tries to delve into the hierarchical structure of public employment service and addresses the problem of rent-seeking in the public sector by government bureaucrats. Chapter 3 studies the wasteful effect of bureaucracy on the economy by addressing the link between rent-seeking behavior of government bureaucrats and the public sector wage bill, which is taken to represent the rent component. In particular, public officials are modeled as individuals competing for a larger share of those public funds. The theoretical model used is calibrated to German data for the period 1970-2007. The analysis then extends to the other major EU economies as well. To illustrate the e ects of scal policy on rent-seeking, the exogenous and the optimal (Ramsey) policy cases are compared and contrasted to one another. The main findings of Chapter 3 are: (i) Due to the existence of a signi cant public sector wage premium and the large public sector employment, a substantial amount of work- ing time is spent rent-seeking, which in turn leads to signi cant losses measured in terms of aggregate output; (ii) The measures for the rent-seeking cost obtained from the model for the major EU countries are highly-correlated to indices of bureaucratic inefficiency; (iii) Under the optimal scal policy regime, steady-state rent-seeking is smaller relative to the exogenous policy case. The benevolent government invests more in public capital, sets a higher public wage premium, but chooses much lower public employment, thus achieving a decrease in rent-seeking.
Additional information: PhD Thesis (Economics), University of Glasgow
Keywords: 330; RBC model; public sectoe